2014
DOI: 10.7314/apjcp.2014.15.2.1005
|View full text |Cite
|
Sign up to set email alerts
|

A New Index of Abdominal Obesity which Effectively Predicts Risk of Colon Tumor Development in Female Japanese

Abstract: Background: A relation between abdominal obesity and colorectal tumor development has been reported repeatedly, and is believed to be more remarkable in man than in women. However, the details vary depending on scientific reports. This may be due at least partly to the selected surface anthropometric index in addition to the influence of gender and ethnic groups. To cope with this, we considered a new index of abdominal obesity and evaluated its risk prediction potential. Materials and Methods: Six hundred nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Since Asians tend to show higher risks for colorectal cancer than other races according to BMI increase27, racial differences cannot be disregarded. A study on Japanese subjects also showed that the association between WHtR and colorectal cancer was more significant in women than in men28, which was similar to the finding in the present study and also serves as an evidence that a racial difference exists. Third, compared to previous studies that used the obesity criteria for Westerners, the present study used more stringent criteria for obesity, which may have led to different results being obtained.…”
Section: Discussionsupporting
confidence: 90%
“…Since Asians tend to show higher risks for colorectal cancer than other races according to BMI increase27, racial differences cannot be disregarded. A study on Japanese subjects also showed that the association between WHtR and colorectal cancer was more significant in women than in men28, which was similar to the finding in the present study and also serves as an evidence that a racial difference exists. Third, compared to previous studies that used the obesity criteria for Westerners, the present study used more stringent criteria for obesity, which may have led to different results being obtained.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple risk factors were identified including increasing age, smoking, black race, obesity, low fibre diet, insulin resistance, and the metabolic syndrome. There is sharp increase in incidence of metabolic syndrome worldwide which is defined as the presence of at least three of the following components: increased waist circumference, hypertriglyceridaemia, low high-density lipoprotein (HDL), hypertension, and hyperglycaemia (Kaneko et al,2014).…”
Section: Introductionmentioning
confidence: 99%
“…16 As a newly developed anthropometric parameter, waist to height index (WHI) was associated with an increased risk of colorectal cancer in female Japanese subjects, but no further study has been reported. 17 Another newly introduced anthropometric parameter, body adiposity index (BAI), has been recognized as an index ofestimating percentage of body fat, but the largely inconsistent results achieved with body adiposity index warrant more explorations of this index.…”
Section: Introductionmentioning
confidence: 99%